Enhancement of the optical and electrical properties of poly ethyl methacrylate/polyvinyl chloride-zinc sulphide (PEMA/PVC@ZnS) ternary nanocomposite films - Nuha Al-Harbi (Heliyon, 2023)
Our research introduces a novel ternary nanocomposite consisting of polyethyl methacrylate/polyvinyl chloride-Zinc sulphide nanoparticles (PEMA/PVC@ZnS). Zinc sulphide (ZnS) nanoparticles were produced via a chemical method and then dispersed at different concentrations (0.02, 0.05, 0.08, and 0.1 wt%) in a single step within the PEMA/PVC blend. The resulting PEMA/PVC@ZnS nanocomposite films were analyzed to investigate their spectroscopic and electrical properties. The dielectric parameters of the samples were also studied in detail. X-ray diffraction (XRD) data indicated an increase in the amorphous region and demonstrated the interaction between ZnS and PEMA/PVC. Fourier transform infrared (FT-IR) results confirmed the specific interactions in PEMA/PVC@ZnS nanocomposites. The synthesized films showed a distinct absorption band at 432 nm, which was attributed to the ZnS surface plasmon resonance. As the concentration of ZnS in PEMA/PVC increased, the band gap energies decreased for both direct and forbidden transitions. Optical parameters such as the extinction coefficient (k), refractive index (n), dielectric constants (ε′ and ε''), optical conductivity (σ(opt.), and photoluminescence (PL) were also studied. The values of dielectric permittivity and dielectric modulus from AC measurement of PEMA/PVC@ZnS nanocomposite films increased with increasing ZnS content. The data suggest that PEMA/PVC@ZnS nanocomposite films exhibit excellent optical and electronic properties, making them suitable for use in various electric and optoelectric applications.